2018
DOI: 10.1200/jco.2017.76.8671
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Analysis in Patients With Cancer: American Society of Clinical Oncology and College of American Pathologists Joint Review

Abstract: Purpose Clinical use of analytical tests to assess genomic variants in circulating tumor DNA (ctDNA) is increasing. This joint review from ASCO and the College of American Pathologists summarizes current information about clinical ctDNA assays and provides a framework for future research. Methods An Expert Panel conducted a literature review on the use of ctDNA assays for solid tumors, including pre-analytical variables, analytical validity, interpretation and reporting, and clinical validity and utility. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
489
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 706 publications
(528 citation statements)
references
References 89 publications
4
489
0
6
Order By: Relevance
“…This wide range may be explained by the various methods used. In the current study as well as in literature, it has been shown that detection rates of ctDNA are dependent on many factors, related to both tumor characteristics and technical aspects (volume of plasma input, method of cfDNA isolation, sequencing techniques and number of interrogated hotspots/genes) . In our cohort, the full spectrum of metastatic disease was included, varying from patients with small metastases, undetectable on standard imaging, to those with only distant lymph node or extensive organ metastases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This wide range may be explained by the various methods used. In the current study as well as in literature, it has been shown that detection rates of ctDNA are dependent on many factors, related to both tumor characteristics and technical aspects (volume of plasma input, method of cfDNA isolation, sequencing techniques and number of interrogated hotspots/genes) . In our cohort, the full spectrum of metastatic disease was included, varying from patients with small metastases, undetectable on standard imaging, to those with only distant lymph node or extensive organ metastases.…”
Section: Discussionmentioning
confidence: 97%
“…As illustrated by the joint review of the American Society of Clinical Oncology and the College of American Pathologists, questions remain about the validity and reproducibility of ctDNA analysis, hampering clinical application . ctDNA detection rates vary widely depending on cancer type and analysis technique; for mPDAC, rates between 38.8% and 86.1% have been reported .…”
Section: Introductionmentioning
confidence: 99%
“…The available data indicate that ctDNA is detectable in a range of pediatric solid tumors at diagnosis, during treatment, and at the time of relapse (Table ). Criteria for determining how ctDNA assays should be adopted into clinical practice were recently outlined in an American Society of Clinical Oncology and College of American Pathologists joint review . They concluded that ctDNA assays must demonstrate (1) analytical validity, meaning the assay is able to detect a targeted variant with accuracy, reproducibility, and reliability; (2) clinical validity, meaning that the assay can divide a clinical group into one or more cohorts with significantly different outcomes; and (3) clinical utility, that the knowledge gained from the assay significantly improves clinical care.…”
Section: Clinical Exploration Of Ctdna In Pediatric Solid Tumorsmentioning
confidence: 99%
“…Therefore, it is hard to expect, that this indirect and potentially error-prone examination of single tumor cells or circulating tumor-specific molecules will indeed replace the direct tissue analysis in the near future. It is also essential to acknowledge, that the majority of actionable mutations demonstrate limited intratumoral heterogeneity; therefore, the analysis of a single tumor lump is usually sufficient for the choice of treatment and liquid biopsy is unlikely to have a high added value for the initial selection of optimal drugs (Jamal-Hanjani et al, 2017; Merker et al, 2018). …”
Section: Liquid Biopsymentioning
confidence: 99%
“…The potential promise of these complex platforms has already been demonstrated in the study of early-stage cancers (Cohen et al, 2018). Nevertheless, many modern varieties of liquid biopsy still require proper clinical validation (Merker et al, 2018). …”
Section: Liquid Biopsymentioning
confidence: 99%